Tempo para colaborar? Olhares sobre o significado e os sentidos atribuídos pelos docentes ao horário de trabalho coletivo - Cardoso, Vania Marques (2015)
This dissertation presents a research named ‘Time to collaborate? Views on the meaning and sense teachers attribute to collective pedagogical work hours’. Our aim was to reveal teachers’ subjective perception of the potential for collaboration during these work hours. The research, based on the Critical Theory school of thought, particularly T. W. Adorno, was completed during 2014 and 2015, approaching the theme of the relevance of collective pedagogical work hours as a social practice at school, focusing on the meaning and sense teachers attribute to them and discussed from its legal, theoretical and empirical perspectives. It approaches the way the contemporary work environment impacts school and teachers’ views of the potential for collaboration of collective work hours and during these hours, how the meaning and sense of these work hours are translated into teachers’ discourses and the proposals for intervention that derive from their discourses. Hypotheses include the ones according to which the contemporary scenery implicates permanent social change and, thus, change at school; that it overburdens teachers, reduces collective pedagogical work and collaboration between peers to the state of usefulness; that the social meaning and the individual sense teachers attribute to their collective pedagogical work hours at school are in an intersection between collaboration potentialities and difficulties and generate a contradictory perception of these work hours as a social practice at school; that teachers’ discourses are full with possibilities of intervention to intensify collaboration potentialities in the collective pedagogical work hours at school. The empirical research methodology involved semi-structured interviews with ten teachers and, from the analysis of their discourse contents, hypotheses were confirmed, and the results allow envisaging possibilities that may be projected in practices to expand collaboration during the collective pedagogical work hours and in further research.